Christentum und Landschaft in Südwest-Ceylon: Eine sozialgeographische Studie - Sievers, Angelika (ERDKUNDE, 1958)
Much of Ceylon may be described as Buddhistic Dagoba landscape. On the other hand certain coastal stretches may be termed Christian landscapes. This is expressed in the spiritual and social structure of the prevailingly Christian population, in the frequency of Christian church and lay buildings and the visible worship of Christian symbols and also in the many social, welfare and cultural institutions which extend their beneficial effects also to the non-Christian population. Only 9 % of the population are Christians, mostly Roman Catholics. The majority belong to the poorer classes, being coastal fishers or labourers on the tea plantations, but there is also a sizeable proportion of the urban intelligentsia in Colombo. The caste system is largely responsible for this. The poor landless population of the western coastal regions became Christianised during the period of Portuguese domination, about 450 years ago, while the rice growing peasants, the strongly feudal Goyigame caste, was barely touched. The Christian cultural landscape is illustrated by three examples taken from the hot humid west coast north of Colombo, between Negombo and Chilaw: First type, a fishing village on the sandspit near Chilaw. 1,300 Singhalese fishers with an admixture of Tamils live in great poverty on the catch of their primitive fishing. They do not even own the coconut palms which shade their thatched huts, they are, however, allowed to pick the coconuts. Their faith and their occupation, they belong to the Karava caste despised by the Buddhists, have welded them into a close community with a social organisation looked after by the church. Second type, the lagoon town Negombo. Of the 32,000 largely Singhalese inhabitants two thirds are Roman Catholics, mostly fishermen, but there are also some people with higher education. Negombo is one of the most important centres of Christian education in Ceylon. The educational efforts of the mission over 400 years have facilitated a social advancement which, as the suppressed Karävas, these people would not have in a Buddhistic social system. Third type, the fishing and market gardening settlement Marawila. The 3,000 inhabitants are mostly Singhalese and almost completely Roman Catholics. Socially there is a clear division into poor fishers with no land of their own and villagers and small holders with mixed tree gardens or coconut groves and plantations. A unity is however achieved through the community of the church and its social institutions as well as equal opportunities of education.